The Risk Assessment and Human Risk Control in Indonesian Power Plant - Jihan Nada Farera; Rita Ambarwati; Sumartik Sumartik; Dedy Dedy (Binus Business Review, 2024)
Efforts to enhance labor productivity are intrinsically linked to the improvement of Occupational Health and Safety (OHS) standards. The research focused on the optimization of OHS by conducting a COVID-19 risk assessment, with the goal of identifying and implementing Human Resource (HR) risk control measures to augment employee performance. In employing a qualitative methodology, the data were amassed through a combination of interviews, observations, and document analysis involving a diverse group of 23 respondents from various departments. The risk assessment process was meticulously structured into four phases: identification of causes, implementation of preventive measures, development of recovery strategies, and evaluation of consequences. The researchers organized the data into primary and secondary categories for analysis and utilized the Bow Tie method to elucidate the findings. The analysis reveals that the human factor, specifically employees’ non-compliance with safety protocols, poses the greatest risk for virus transmission. The result identifies the warehouse, workshop, administration building, and Coal Handling Control Building (CHCB) as the most critical areas requiring stringent risk controls. The results also provide an overview in preparing the basis for Corrective Action and Preventive Action (CAPA). It provides benefits for implementing OHS in power plant companies through recommendations such as evaluation, preventive action, and risk control through COVID-19 risk assessment. Finally, the research delineates strategies for managing risks through preventive measures and recovery processes to mitigate the impacts and consequences associated with these hazards.